Synthesis N1-Tersier-Butilteobromin from Teobromin and Tersier-Butylbromides - Sri Gustini Husein; Achmad Zainuddin; Sani Hoeruman (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Xantine derivatives are known to have some pharmacological activity, such as a bronchodilator. The substitution on atoms N1 xantine can improve the activity and selectivity as a tracheaspasm. The purpose of this research was to investigate the influence of concentration sodium hydroxide in sodium acetate as solvent used on the production yield of N1-tert-butilteobromin. The result of the synthesis was isolated using chloroform and purified with the preparative thin layer chromatography. The molecule structure of N1-tert-butilteobromin was confirmed using ultraviolet and infrared spectrophotometry. The result showed that sodium hydroxide concentration could effect the results of yield. The yields of 4%, 8%, and 12% sodium hydroxide concentration were 3.7% (0.074 g), 7.2% (0.144 g), and 1.3% (0.026 g), respectively.Keywords: N1-tert-butylteobromin, sodium hydroxide, tert-butylbromide, theobromine